Virtual MIMO schemes for downlink space-frequency coding OFDM systems - Teodoro, S.
In this paper we investigate the performance of single-relay cooperative scheme, where the source is equipped with a 2-antenna array and both the relay and destination with a single antenna. We consider Amplify-and-Forward, Decode-and-Forward and Selective Decode-and-Forward relaying protocols and a space-frequency block coding designed for DL OFDM based systems is employed. Signals expressions are derived for each relay protocol under various scenarios, considering power constraint imposed on cooperating nodes. The aim of this work is to evaluate this Virtual MIMO scheme in realistic scenarios (e.g. correlated antennas, precise channel models, Doppler effects) for implementation purposes in a system with LTE based parameters and considering channel turbo coding. The coded performance of the proposed Virtual MIMO scheme is evaluated, and compared against non-cooperative OFDM based systems, for typical pedestrian scenarios based on LTE specifications. The proposed cooperative scheme outperforms the co-located MISO and MIMO for some scenarios.